Impact of Clinical Pharmacist Interventions and Tele-Monitoring on Clinical Outcomes of Type-2 Diabetes Mellitus Patients - Ramidi, Swetha Reddy; Vancha, Manasa; Guggila, Vamshi; Fathima, Syeda Nishat; Reddy K, Satyanarayana; Manda, Rama; Sindgi, Vasudeva Murthy (Indian Journal of Pharmacy Practice)
Background: Since the occurrence of diabetes is increasing, contact between doctor and patient, decreasing, hence as the effective counselling which projects a need for the clinical pharmacist. Aim: To evaluate the outcome among Type 2 diabetes mellitus (T2DM) patients after interventions and tele-monitoring by clinical pharmacist. Patients and Methods: This is a prospective study conducted with a sample size of 140 T2DM patients. The intervention program included patient education and counselling. Patients after assessment of blood glucose parameters, giving information on diabetes and medication adherence and patients received counselling from clinical pharmacist are included in the study. Follow-up was done periodically through phone calls for assessment of health. Blood glucose parameters such as postprandial blood glucose levels (PLBS), Fasting Blood Glucose (FBG), Glycosylated Haemoglobin (HbA1c) and familiarity about knowledge on diabetes, medication adherence were reassessed after 3-month intervention. Results: There was a significant improvement in FBG, HbA1c, PLBS, diabetes knowledge, medication adherence among patients after intervention by the clinical pharmacist. Conclusion: Standard counselling and regular follow-up by the clinical pharmacists will improve the glycaemic control among diabetes patients and the role played by clinical pharmacists in educating patients about diabetes management is noticeable.
Keywords: Glycosylated haemoglobin; Morisky Green Levine Scale; Tele-monitoring; Post prandial blood sugar; Type 2 diabetes mellitus.